2013
DOI: 10.17221/140/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light availability on leaf area index, biomass production and plant species composition of park grasslands in Warsaw

Abstract: How light conditions affect development of park grasslands is a question that has not been satisfactory addressed. The aim of this study was therefore determination of the level to which unfavorable light conditions influence grassy parks area and relationships between parameters which determine state of turf grasses. Researches were conducted in two parks in Warsaw, in various light conditions and included measurement of: leaf density, sward height, leaf area index (LAI), and botanical composition of the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…The applied plants should be characterized by low fertilizer, water, and pesticide requirements, high efficiency of the photosynthetic apparatus, and they should be well adapted to the local climate [44]. Previous research [45,46] and the present findings indicate that PTE impair chlorophyll synthesis and decrease the chlorophyll content of plants. Plant resistance to toxic levels of PTE varies across species and varieties.…”
Section: Discussionsupporting
confidence: 50%
“…The applied plants should be characterized by low fertilizer, water, and pesticide requirements, high efficiency of the photosynthetic apparatus, and they should be well adapted to the local climate [44]. Previous research [45,46] and the present findings indicate that PTE impair chlorophyll synthesis and decrease the chlorophyll content of plants. Plant resistance to toxic levels of PTE varies across species and varieties.…”
Section: Discussionsupporting
confidence: 50%
“…The negative infl uence of shade on leaf area was confi rmed also by Dai et al (2009) and Mirales et al (2011). Results obtained by Dąbrowski et al (2013) shown that shading has a strong infl uence on soding area on parks lawns.…”
Section: Results and Discusionmentioning
confidence: 99%
“…The lawn varieties of Perennial ryegrass (Lolium perenne L.) are commonly used for establishing the lawns in urban areas (Dąbrowski et al 2013). The answer to following questions: what is the capability of detect the stress caused by shade in tested lawn varieties of Perennial ryegrass by using the chlorophyll a fl uorescence measurements (O-J-I-P test) and which of tested variety has the best properties to create grasslands under reduced light conditions is the main aim of this work.…”
Section: Introductionmentioning
confidence: 99%
“…The canopy height also correlates and influences the structural characteristics and the mass of the forage (Santos et al, 2017), making possible the understanding of these structures and the behavior of the animals to plant variations (Fonseca et al, 2013). Dabrowski et al (2013) found a high correlation coefficient between plant height and leaf area index.…”
Section: Effect Of Wood Ash and Soil Water On Plant Heightmentioning
confidence: 99%